El fenómeno de El Niño: Oscilación del Pacífico Sur (ENSO). Aplicación didáctica - Gonzales Montoya, Yuliza Dayra (2019)
The origin and heating of the waters of the Pacific Ocean mainly affect to Southeast Asia. El Niño affects Australia and South America, we can evidence its characteristics when we see a quantity of warm waters that are located in the sea from bordering the coasts of the north of the country, causing an increase in climatic changes abnormal projection. We appreciate that the increase in sea temperature comes considerably affecting productive activities such as fishing. The proceeding of your reference is from the child Jesus. we can also say that this phenomenon with a characteristic name occurs in the Pacific Ocean in direction of the west coast of South America around Christmas. The denomination applicable to this fact is the abbreviation in English of El Niño Southern Oscillation, ENSO. This is a syndrome that has been going on for more than 7,000 years. Meteorologist Abraham Levy pointed out that the reason for this phenomenon is that traditionally the cold sea in the autumn season warms up as in winter, which causes the overall temperature to rise.